Interventions for the Treatment of Aromatase Inhibitor–Associated Arthralgia in Breast Cancer Survivors: A Systematic Review and Meta-analysis. Issue 4 (July 2017) - Yang, Gee Su; Kim, Hee Jun; Griffith, Kathleen A.; Zhu, Shijun; Dorsey, Susan G.; Renn, Cynthia L.
Abstract : Background: Aromatase inhibitors (AIs) have been established as successful adjuvant therapy for breast cancer survivors. Unfortunately, nearly half of women taking AIs report joint pain, AI-associated arthralgia (AIA). Aromatase inhibitor–associated arthralgia often results in noncompliance, which could lead to cancer recurrence. Objective: The purpose of this study was to identify current pain management of AIA and to evaluate the study quality and effects of interventions. Methods: Nineteen articles published from 2000 to August 2015 were identified using PubMed, CINAHL, PsycINFO, Web of Science, and additional records. Study quality was evaluated by the Quality Assessment Tool for Quantitative Studies. Meta-analysis was used to obtain effect sizes of interventions on pain and subgroups. Results: Five types of interventions emerged: pharmacological approaches, acupuncture, nutritional supplementation, relaxation techniques, and physical exercise. Six studies were strong, 8 were moderate, and 5 were weak in quality. The overall effect size of the interventions on pain was large; pharmacological approaches, acupuncture, and relaxation techniques showed moderate to large effects on pain, whereas nutritional supplementation and physical exercise had no significant effects on it. Conclusion: The evidence was based on a body of research with moderate study quality. Although the overall effect of interventions is large, further investigation into the influence of nutrition and physical exercise is needed to better discern their potential for pain management. Implication for Practice: Oncology nurses may be able to implement such validated interventions as pain management modalities to mitigate the symptoms so that breast cancer survivors remain compliant with AIA therapy.